2020
DOI: 10.1111/liv.14420
|View full text |Cite
|
Sign up to set email alerts
|

Liver imaging reporting and data system category M: A systematic review and meta‐analysis

Abstract: Background and Aims:The Liver Imaging Reporting and Data System (LI-RADS) category M (LR-M) was introduced to preserve the high specificity of LI-RADS algorithm for diagnosing hepatocellular carcinoma (HCC). We aimed to systematically determine the probability of the LR-M for HCC and non-HCC malignancy, and to determine the sources of heterogeneity between reported results. Methods:Original studies reporting the probability of LR-M for HCC and non-HCC malignancy on magnetic resonance imaging (MRI) were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Meanwhile, rim APHE on CEUS showed the lowest pooled frequency (30%) in non-HCC malignancies. This finding contrasts with the results of a previous meta-analysis using CT/MRI, where rim APHE had the highest frequency in non-HCC malignancies [ 8 ]. Differences in imaging modalities and contrast agent properties may have contributed to the observed differences in the frequencies of imaging features using CEUS or CT/MRI.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, rim APHE on CEUS showed the lowest pooled frequency (30%) in non-HCC malignancies. This finding contrasts with the results of a previous meta-analysis using CT/MRI, where rim APHE had the highest frequency in non-HCC malignancies [ 8 ]. Differences in imaging modalities and contrast agent properties may have contributed to the observed differences in the frequencies of imaging features using CEUS or CT/MRI.…”
Section: Discussioncontrasting
confidence: 99%
“…The present meta-analysis revealed that the proportion of overall malignancies in the CEUS LR-M category was high (94%), with similarity to the proportion of the CT/MRI LR-M (93%) category reported in a previous meta-analysis [ 23 ]. However, the pooled proportion of HCC in the LR-M category was higher using the CEUS LI-RADS (54%) than the CT/MRI LI-RADS (22%-36%), and the pooled proportion of non-HCC malignancies was lower using the CEUS LI-RADS (40%) than the CT/MRI LI-RADS (57%-77%) [ 8 , 23 , 24 ]. This discrepancy in the pooled proportion between CEUS and CT/MRI LI-RADS was similar in the subgroup analysis of the present study that included only cohort studies (HCC 59% and non-HCC malignancies 36% in the CEUS LR-M).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another two meta-analyses determined the sensitivity and specificity of LR5 for diagnosing HCC using CT/MRI LI-RADS and CEUS LI-RADS, respectively [15,16]. Kim et al focused on the probability of HCC and OM in the LRM based on MRI [17]. Nevertheless, no systematic review or meta-analysis has compared the diagnostic performance of CEUS LI-RADS and CT/MRI LI-RADS for characterizing HCC and OM.…”
Section: Introductionmentioning
confidence: 99%